Effects of Low-Dose Pioglitazone on Serum Levels of Adiponectin, Dehydroepiandrosterone, Amyloid Beta Peptide, and Lipid Profile in Elderly Japanese People with Type 2 Diabetes. (21st October 2015) - Aoki, Yuji
Abstract : This study was performed to see how pioglitazone at low doses could affect blood biomarkers related to atherosclerosis and aging. The effects of an add-on treatment with pioglitazone (15 mg for males and 7.5 mg for females) for 6 months were assessed in 24 outpatients (12 males, 12 females) with type 2 diabetes aged ≥ 70 years. As doses of sulfonylurea were reduced in 10 patients, no significant differences in HbA1c and glucose levels were seen. After the treatment, serum levels of HDL cholesterol, arachidonic acid (predominant in males), and high-molecular-weight adiponectin significantly increased. The level of dehydroepiandrosterone sulfate significantly decreased. No significant changes were seen in those of small dense LDL cholesterol, high-sensitivity C-reactive protein, and amyloid beta peptides 1–40 and 1–42. There was a slight but significant increase in body weight, but apparent adverse effects were not observed. In conclusion, pioglitazone at low doses increased serum adiponectin, HDL cholesterol, and arachidonic acid levels but decreased serum dehydroepiandrosterone level, not associated with glycemia, in elderly Japanese people with type 2 diabetes. An optimal dose of pioglitazone should be sought for to minimize its adverse effects and to fully exert its pleiotropic effects such as antiatherosclerotic and antiaging effects.